Digital pioneers in rural regional development: A bibliometric analysis of digitalisation and leadership; Digitale Pioniere in der ländlichen Regionalentwicklung: Eine bibliometrische Analyse zu Digitalisierung und Leadership - Julia Binder; Antje Witting (Raumforschung und Raumordnung / Spatial Research and Planning, 2022)
While research into digitalisation in cities has grown strongly in recent years, rural areas have now also clearly shifted into the focus of attention. An important strand of research into digitalisation in rural areas can be described as agency perspectives. Current studies point to the driving, transformative force of key figures, for example social entrepreneurs, smart villagers or spatial pioneers. At heart, these studies propose that paths for collective action can be developed via key figures, thus generating ways to change established rules and norms. This paper represents a methodological contribution to this strand of research by subjecting the debate on leadership through key figures to a quantitative, bibliometric analysis, on the basis of which a heuristic is proposed in order to develop relevant research questions. Based on different strands of discourse, our results show that unequal spatial development ismanifested in an urban bias, but also demonstrate the potential of the growing research field in rural regional development. – – Während das Forschungsfeld zu Digitalisierung in Städten zuletzt stark angewachsen ist, rücken nun auch ländliche Räume deutlich in den Fokus. Ein wichtiger Forschungsstrang zur Digitalisierung in ländlich geprägten Räumen kann als agency perspective beschrieben werden. Aktuelle Studien verweisen auf die treibende transformative Kraft von Schlüsselfiguren, beispielsweise social entrepreneurs, smart villagers oder spatial pioneers. Sie vertreten im Kern die Annahme, dass über Schlüsselfiguren Pfade für gemeinschaftliches Handeln entwickelt werden und es so zu Veränderungen in den bestehenden Regelwerken und Normen kommen kann. Dieser Aufsatz leistet einen methodischen Beitrag zu diesem Forschungsstrang, indem er über eine quantitative bibliometrische Analyse die englischsprachige Debatte zu leadership durch Schlüsselfiguren analysiert und daran folgend eine Heuristik vorschlägt, um Fragen zu entwickeln. Unsere Ergebnisse zeigen anhand unterschiedlicher Diskursstränge die ungleiche räumliche Entwicklung im Sinne eines urban bias, aber auch das Potenzial eines wachsenden Forschungsfeldes in der ländlichen Regionalentwicklung auf.
Keywords: 710; Digitalisation; regional development; digital pioneers; leadership; bibliometric analysis; Digitalisierung; Regionalentwicklung; digitale Pioniere; leadership; bibliometrische Analyse